Accelerated eutrophication and toxicity in tropical reservoir water and sediments: an ecotoxicological approach - Rietzler, A. C.; Botta, C. R. [UNESP]; Ribeiro, M. M.; Rocha, O.; Fonseca, A. L. (Springer, 2018)
The aim of this study was to jointly show the results of three independent ecotoxicological studies performed to investigate pollutants in three Brazilian tropical reservoirs undergoing accelerated eutrophication. In order to accomplish this goal, the full toxicity identification and evaluation procedure (TIE approach) was performed, at Pampulha (Minas Gerais State) and Salto Grande and Bana Bonita reservoirs (Sao Paulo State). Acute and chronic toxicity tests were performed using the cladocerans Daphnia similis and Ceriodaphnia dubia (exotic) and Daphnia laevis and Ceriodaphnia silvestrii (native) as test organisms. Results from TIE procedure stage I indicated the existence of nonpolar organic and filterable compounds in the water from Pampulha, probably cyanotoxins, and oxidants as part of the toxic agents. TIE results for sediments identified ammonia (Pampulha and Salto Grande), organic compounds (Pampulha), metals (Pampulha, Barra Bonita, and Salto Grande), and acidity (Salto Grande) as responsible for toxicity. Whole-sediment remediation experiments for Pampulha reservoir confirmed, through reproduction decrease, ammonia and organic compounds as contaminants. Such pollutants represent threats to aquatic biota and must be prevented. Higher temperatures as predicted from global climate change will severely affect tropical shallow reservoirs, accelerating eutrophication, the release of contaminants from sediments, and increasing toxicity.
Keywords: Ecotoxicology; Freshwater contaminants; Cladocerans; Cyanobacteria; Ammonia; Metals; Remediation